Photocatalytic degradation of p-chlorophenol by hybrid H2O2 and TiO2 in aqueous suspensions under UV irradiation. (1st January 2015) - Nguyen, Anh Thu; Juang, Ruey-Shin
Abstract: In this study, TiO2 particles were used as photocatalysts for the degradation of aqueous p -chlorophenol ( p -CP) under UV irradiation. The effect of TiO2 dose (0–3 g/L), initial p -CP concentration, H2 O2 concentration (2–45 mM), solution pH (4.6–9.5), and UV light intensity on the degradation of p -CP were examined. Four oxidative degradation processes, which utilized UV alone (direct photolysis), H2 O2 /UV, TiO2 /UV, and H2 O2 /TiO2 /UV, were compared in a batch photoreactor with a 100-W high-pressure mercury lamp. The photodegradation of p -CP could be described by the pseudo-first-order kinetics according to the Langmuir–Hinshelwood model. Moreover, the apparent degradation rate constants increased considerably from 3.5 × 10 − 3  min − 1 (direct photolysis) to 19.9 × 10 − 3  min − 1 (H2 O2 /TiO2 /UV system). Highlights: The hybrid H2 O2 /TiO2 /UV process could enhance photodegradation of p -chlorophenol. Photodegradation of p -chlorophenol under UV irradiation well followed the L–H model. The apparent rate constant nearly double increases compared to the absence of H2 O2 . TiO2 dose should be optimized before selection of other variables in photocatalysis.